A felmondás szabályozása az elmúlt 30 évben Különös tekintettel a munkáltató működésével összefüggő indokra - Szita Natasa (A Pázmány Péter Katolikus Egyetem Jog- és Államtudományi Karának Könyvei. Doktorandusz Tanulmányok, 2020)
This article off ers a summary of the changes of the Hungarian dismissal law after the political changeover and the transition to a market economy. The paper fi rst introduce the dismissal law regulation under the previous Labour Code and highlights the main cases which have the greatest eff ects on the practices of the court, such as MK 95. and MK 154. It then focuses on the dismissal regulation of the operative Act I of 2012 on the Labour Code, and the eff ects and the response to the economical and fi nancial crisis. In this context the article examines which atypical works can be a resolution for the changing labour market. Finally, in the summary the general fi ndings of the paper are presented.